Superstition in Surgery: A Population-Based Cohort Study to Assess the Association Between Surgery on Friday the 13th and Postoperative Outcomes - Sanjana Ranganathan, MBE; Carlos Riveros, MD; Michael Geng, BS; Courtney Chang, MD; Yusuke Tsugawa, MD, MPH, PhD; Bheeshma Ravi, MD, PhD; Zachary Melchiode, MD; Siqi Hu, MD, PhD; Kathleen Kobashi, MD, MBA; Brian J. Miles, MD; Zachary Klaassen, MD, MSc; Avery Nathens, MD, MPH, PhD; et al. (Annals of Surgery Open)
Objective:. We sought to examine whether the outcomes of patients who receive a surgical procedure on Friday the 13th differ from patients who receive surgery on flanking Fridays. Background:. Numerous studies have demonstrated that increased anxiety from the provider or patient around the time of surgery can lead to worse outcomes. Superstitious patients often express significant concern and anxiety when undergoing a surgical procedure on Friday the 13th. Methods:. A retrospective, population-based cohort study of 19,747 adults undergoing 1 of 25 common surgical procedures on Friday the 13th or flanking control Fridays (Friday the 6th and Friday the 20th) between January 1, 2007, and December 31, 2019, with 1 year of follow-up. The main outcomes included death, readmission, and complications at 30 days (short-term), 90 days (intermediate-term), and 1 year (long-term). Results:. A total of 7,349 (37.2%) underwent surgery on Friday the 13th, and 12,398 (62.8%) underwent surgery on a flanking Friday during the study period. Patient characteristics were similar between the 2 groups. We found no evidence that patients receiving surgery on Friday the 13th group were more likely to experience the composite primary outcome at 30 days [adjusted odds ratio (aOR) = 1.02 (95% CI = 0.94–1.09)], 90 days [aOR = 0.97 (95% CI = 0.90–1.04)], and 1 year [aOR = 0.99 (95% CI = 0.94–1.04)] after surgery. Conclusion:. Patients receiving surgery on Friday the 13th do not appear to fare worse than those treated on ordinary Fridays with respect to the composite outcome.